2018
DOI: 10.1109/tcns.2017.2763745
|View full text |Cite
|
Sign up to set email alerts
|

Transient Response Improvement for Interconnected Linear Systems: A Low-Dimensional Controller Retrofit Approach

Abstract: Abstract-In this paper, we propose a method of designing low-dimensional retrofit controllers for interconnected linear systems. In the proposed method, by retrofitting an additional low-dimensional controller to a preexisting control system, we aim at improving transient responses caused by spatially local state deflections, which can be regarded as a local fault occurring at a specific subsystem. It is found that a type of state-space expansion, called hierarchical state-space expansion, is the key to system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Analyzing the transient characteristics of an SLG fault, it is found that the transient process contains varies frequency [11][12]. The principal frequency component has the largest energy, which can be used to represent the characteristics of the transient process.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the transient characteristics of an SLG fault, it is found that the transient process contains varies frequency [11][12]. The principal frequency component has the largest energy, which can be used to represent the characteristics of the transient process.…”
Section: Introductionmentioning
confidence: 99%